ENHANCING CONCRETE PERFORMANCE: A REVIEW OF SELF-CURING CONCRETE INCORPORATING POLYETHYLENE GLYCOL (PEG) (International Journal of Engineering Management Science, 2024)
Self-curing concrete has emerged as a promising solution to address the challenges associated with traditional water curing methods. Polyethylene glycol (PEG) is one of the most commonly used self curing agents due to its ability to absorb and retain moisture within the concrete matrix. This review paper provides a comprehensive overview of the use of PEG in self-curing concrete, focusing on its effects on properties such as compressive strength, permeability, and durability. The paper discusses the mechanism of PEG in self-curing concrete, highlighting its role in promoting hydration and reducing shrinkage. Furthermore, the challenges and limitations associated with the use of PEG, such as cost and potential effects on setting time, are discussed. Future research directions to enhance the effectiveness of PEG in self-curing concrete are also suggested.
Keywords: self-curing concrete, polyethylene glycol, compressive strength, permeability, durability, hydration, shrinkage, challenges, future directions